Factors associated with zinc prescription practice among children with diarrhea who visited public health facilities in Addis Ababa, Ethiopia: A cross sectional study - Woldegebriel, Abenezer; Beyero, Mesfin; Daba, Alemneh Kabeta (Journal of Advanced Pediatrics and Child Health, 2021)
Background: Diarrhea and nutrient deficiency worsen each other, and zinc is recommended to be included in clinical management of diarrhea. Therefore, this investigation was done to assess zinc prescription practice to children with diarrhea, identify factors associated with zinc prescription, and assess caregivers’ zinc’s perceived cost and willingness to pay for. Methods: A health institution based cross-sectional study was done. Caretakers of 609 children with diarrhea attending health centers in Addis Ababa were included. Logistic regression was applied to identify variables associated with zinc prescription. Results: Zinc was prescribed to 62.1% of children. About 74.9% of the caregivers were willing to pay for zinc. Previous use of zinc (AOR = 2.3; 95% CI: 1.34-4.01), exposure to zinc related message (AOR = 2.6, 95% CI: 1.53-4.60) and willingness to pay for zinc (AOR = 6.9; 95% CI: 3.84-12.66) were associated with zinc prescription. Conclusion: Zinc was not administered to considerable proportion of children with diarrhea. Previous use of zinc, exposure to zinc related message and willingness to pay for positively contributed to zinc prescription. Health care workers shall be encouraged on zinc prescription. Intervention to increase willingness to pay for zinc and zinc benefit communication shall be strengthened in parallel with operational researches.